Dopamine modulation of chemotactic behavior in response to natural aroma substances in Drosophila melanogaster larvae - Tomoko Shibuya; Takahisa Nakane; Akihito Takano; Junji Yamauchi; Takako Morimoto (Elsevier, 2021)
Background: Organisms perceive various sensory information from the outside world and use this information to initiate several actions. In particular, odors are strongly linked to emotion and often evoke different feelings and specific memories. Aromatic substances are volatile essential oils extracted from plants, each containing more than 200 types of organic compounds, and they are known as distinctive odors that interact with emotion. However, the mechanisms of how aromas cause emotion, for example, feelings of like or dislike that elicit attractive or aversive behavior, have not yet been elucidated. Purpose: To reveal the mechanisms, we studied aroma-induced behaviors using Drosophila melanogaster larvae. We focused on the involvement of dopamine in the chemotactic behavior in response to aromas. Methods: First, the larval chemotactic behavior was examined using 37 types of essential oils in three concentrations (100, 10−1, and 10−2dilutions). We then investigated the involvement of dopamine in chemotactic behavior since it is well known as a neuromodulator related to emotion. Results: We found that most of these substances elicited larval attractive behavior and identified the following essential oils as attractive odors: German chamomile, ylang-ylang, cajeput, pine, eucalyptus lemon, spikenard, ginger, cypress, pepper, clove, cinnamon cassia, citronella java, and Roman chamomile. However, some other substances induced neutral or aversive behavior, and Ho wood was determined to be an aversive odor in the screening experiment. Interestingly, the inhibition of dopamine transmission suppressed the attractive behavior in response to aromatic substances and to a larval food or yeast paste, but not to the odor of a single chemical compound. Conclusion: These results suggest that there is a distinct neural mechanism underlying the behavior that is induced by aromatic substances.